Bombesin-like peptide mediates lung injury in a baboon model of bronchopulmonary dysplasia. - Sunday, M E (1998)
The etiology of bronchopulmonary dysplasia (BPD), a chronic lung disease of infants surviving respiratory distress syndrome, remains fundamentally enigmatic. BPD is decreasing in severity but continues to be a major problem in pediatric medicine, being especially prevalent among very premature infants. Increased numbers of pulmonary neuroendocrine cells containing bombesin-like peptide (BLP) have been reported to occur in human infants with BPD. We tested the hypothesis that BLP mediates BPD using the hyperoxic baboon model. Urine BLP levels increased soon after birth only in 100% O2-treated 140-d animals which developed BPD, correlating closely with severity of subsequent chronic lung disease. Similar elevations in urine BLP were observed in the 125-d baboon "interrupted gestation" model of BPD. Postnatal administration of anti-BLP antibody attenuated clinical and pathological evidence of chronic lung disease in the hyperoxic baboon model. Urine BLP could be a biological predictor of infants at risk for BPD, and blocking BLP postnatally could be useful for BPD prevention.